Private provision of public goods : neutrality and wealth-dependent preferences (2012)
Several authors have investigated the bounds of the so-called neutrality theorem where public goods are privately provided. Following this line of analysis, I investigate further in this paper the bounds of this result. I concentrate on an unexplored case in the existing literature- namely that where individual preferences for a public good are affected by respective levels of individual wealth. I prove that under such circumstances, the neutrality theorem no longer holds. More appealing, I discuss the conditions under which a redistribution of wealth might improve efficiency in the aggregate provision of public goods. Interestingly, we find that a redistribution of wealth from individuals who have a low valuation for public goods to those who have a high valuation for public goods does not necessarily increase its aggregate provision.